Kamen's quick clustering of participation data: A research note - L. Pitt; D. Nel (South African Journal of Business Management, 1988)
– This brief research note revisits a simple, but very useful clustering procedure developed by Kamen (1970), and illustrates its use in the clustering of attitudinal/perceptual data. For the purpose of illustrating the technique, perceptions of peer group participation in potentially corrupt situations in business were used as the data set. The mean responses, standard deviations and medians of 458 managers served as input for a correlation matrix from which the variables were clustered. The clusters formed by the analysis have been interpreted as 'The Insiders', 'Felons', 'Happy Holidays', 'The Fiddlers', 'A Bit on the Side', and 'The Innocents'. From the clusters identified it was evident that some situations were similar in nature. Quick clustering of the pilot study data is regarded as successful and could therefore lead to improved questionnaire design as well as the elimination of similar questions.
Keywords: 650